Aging in Central America and the Caribbean - Roberth Steven Gutiérrez Murillo (Oswaldo Cruz Foundation, Health Law Program, 2021)
The book Aging in Central America and the Caribbean, object of this review, was published in 2018 by Centro de Investigaciones sobre América Latina y el Caribe (CIALC), from the Universidad Autónoma de México, and organized by Aída Díaz-Tendero Bollain. The work addresses aging in Latin America and the Caribbean from a multidisciplinary perspective of the phenomenon under the prism of human rights, socio-economic aspects and demographic elements in the region. An important analysis is the privatization of health and social assistance services, which triggered the rupture of ties of intergenerational solidarity and challenged the continuity of economic solidarity for the elderly.